Etiology and Prognosis of Cardiogenic Shock in a Secondary Center without Surgical Back-Up - Laurent Bonello; Marc Laine; Etienne Puymirat; Victoria Ceccaldi; Mélanie Gaubert; Franck Paganelli; Pr Franck Thuny; Thibaut Dabry; Guillaume Schurtz; Clement Delmas; Julien Mancini; Gilles Lemesle (Cardiology Research and Practice)
Background. Cardiogenic shock (CS) remains a major challenge in contemporary cardiology. Data regarding CS etiologies and their prognosis are limited and mainly derived from tertiary referral centers. Aims. To investigate the current etiologies of cardiogenic shock and their associated short- and long-term outcomes in a secondary center without surgical back-up. Methods. We performed an observational prospective monocenter study. All patients admitted for a first episode of CS related to left ventricular dysfunction were enrolled. The definition of CS was consistent with the European Society of Cardiology guidelines. Patients were followed for 6 months. Etiologies were analyzed, and survival rates derived from Kaplan-Meier estimates were compared with the log-rank test. Results. Between January 2015 and January 2016, 152 patients were included. The first most common cause of CS was acute decompensation of chronic heart failure (CHF). Acute coronary syndromes (ACS) were the second most common cause of CS (35.4%). At one month, the all-cause mortality rate was 39.5% and was similar between ACS and CHF (43% vs 35%, respectively; p=0.7). In a landmark analysis between 1 and 6 months, we observed a significantly higher mortality in patients with CHF than in patients with ACS (18% vs. 0%; p=0.01). Conclusions. In the present registry, acute decompensation of chronic heart failure was the most common cause of CS, while ACS complicated by CS was the second most common cause. Of importance, acute decompensation of CHF was associated with a significantly worse outcome than ACS in the long term.